Vulvar Lobular Capillary Hemangioma: A Rare Location for a Frequent Entity. (29th December 2016) - Abreu-dos-Santos, F.; Câmara, S.; Reis, F.; Freitas, T.; Gaspar, H.; Cordeiro, M.
Abstract : Lobular capillary hemangioma, or pyogenic granuloma, is an acquired hemorrhagic benign vascular lesion of the skin and mucous membranes. The pyogenic granuloma of the vulva is a rare finding and a limited number of case reports are available in the literature. To the best of our knowledge this is the first case described as a single pyogenic granuloma on the vulva.